Mbili Mbili Cropping Systems for crop diversification and climate resilience: IPSR Innovation Profile - Waswa, Boaz Shaban; Kihara, Job Maguta; Kinyua, Michael; Ooro, Patrick (2022)
Mbili Mbili intercropping system has been promoted as a crop diversification and intensification approach. Mbili-Mbili exploits plant spatial configurations to increase light penetration to the legumes, otherwise often shaded by cereals. The main aim is to increase legume productivity, while maintaining the same productivity of the cereal and taking advantage and complementarity of the different growth habits and durations of the combined crops. Mbili Mbili enables a farmer to grow both legumes and cereals on the same land and thus harvest at different times. In event of a loss, one crop serves as an insurance. This makes the system climate smart. Mbili Mbili system has been reported to have a higher return (up to 37% more) compared to the standard farmer intercropping practices. The technology has been tested, and widely promoted in maize growing areas in Kenya and other countries in east and southern Africa.